Drosophila Hfp negatively regulates dmyc and stg to inhibit cell proliferation. - Quinn, L.M.; Dickins, R.A.; Coombe, M.; Hime, G.R.; Bowtell, D.D.; Richardson, H. (Development, 2004)
Mammalian FIR has dual roles in pre-mRNA splicing and in negative transcriptional control of Myc. Here we show that Half pint (Hfp), the Drosophila orthologue of FIR, inhibits cell proliferation in Drosophila. We find that Hfp overexpression potently inhibits G1/S progression, while hfp mutants display ectopic cell cycles. Hfp negatively regulates dmyc expression and function, as reducing the dose of hfp increases levels of dmyc mRNA and rescues defective oogenesis in dmyc hypomorphic flies. The G2-delay in dmyc-overexpressing cells is suppressed by halving the dosage of hfp, indicating that Hfp is also rate-limiting for G2-M progression. Consistent with this, the cycle 14 G2-arrest of stg mutant embryos is rescued by the hfp mutant. Analysis of hfp mutant clones revealed elevated levels of Stg protein, but no change in the level of stg mRNA, suggesting that hfp negatively regulates Stg via a post-transcriptional mechanism. Finally, ectopic activation of the wingless pathway, which is known to negatively regulate dmyc expression in the wing, results in an accumulation of Hfp protein. Our findings indicate that Hfp provides a critical molecular link between the developmental patterning signals induced by the wingless pathway and dMyc-regulated cell growth and proliferation.